Tripeptides featuring dehydrophenylalanine and homophenylalanine: homo- versus hetero-chirality and sequence effects on self-assembly and gelation - Carvalho, André F. (2025)
Over the years, our research group developed dehydrodipeptides N-capped with aromatic moieties as protease-resistant efficacious hydrogelators, affording self-assembled hydrogels at low (critical) concentrations. Dehydrotripeptides, with different dipeptide sequences and (D,L) stereochemistry, open a wider chemical space for the development of self-assembled soft nanomaterials. In this work, a small library of N-succinylated dehydrotripeptides containing a C-terminal dehydrophenylalanine (∆Phe) residue and a scrambled dipeptide sequence with phenylalanine (Phe) and homophenylalanine (Hph) (L-Phe-L,D-Hph and L,D-Hph-L-Phe) was synthesized and characterized as a potential hydrogelator. Two pairs of diastereomeric tripeptides were synthesized, both as Cprotected methyl esters and as deprotected dicarboxylic acids. Peptides with the sequence Hph-Phe-Phe were obtained as a pair (D,L,Z)/(L,L,Z) of diastereomers. Their scrambled sequence analogues Phe-Hph-Phe were obtained also as a diastereomeric (L,D,Z)/(L,L,Z) pair. The effect of stereochemistry (homo- vs. hetero-chirality) and sequence (Phe-∆Phe vs. Hph-∆Phe motif) on the self-assembly, biocompatibility, gelation and rheological properties of the hydrogels was studied in this work. Accessible, both as C-protected methyl esters and as dicarboxylic acids, N-succinylated dehydrotripeptides are interesting molecular architectures for the development of supramolecular nanomaterials. Interestingly, our results do not comply with the well-documented proposition that heterochiral peptides display much higher self-assembly propensity and gelation ability than their homochiral counterparts. Further studies will be necessary to fully understand the interplay between peptide sequence and homo- and hetero-chirality on peptide self-assembly and on the properties of their supramolecular materials.